Dinâmica da política externa brasileira: uma análise do conceito de autonomia - Eiras, André Luis Silva (2023)
The search for autonomy is a Brazilian foreign policy project that has been pursued more actively by the nation since the twentieth century. Its basic premise is to define the national interest to qualify and provide an internal modernization, both in the political and economic, and social sectors, that functions adequately within the capitalist international system. This paper aims to analyze the historical construction of this concept and understand its role in the past and present. The central hypothesis here is that the concept of autonomy in foreign policy did not emerge exclusively within the state bureaucratic framework (Ministry of Foreign Affairs), but that it took place in conjunction among Brazilian academic intellectuals, politicians, and diplomats since the mid-1950s. We will use for our analysis the definition of foreign policy as a partially autonomous and structured social space, in which academia and bureaucratic diplomacy play for power to have their ideas implemented. We will observe the trajectory of the concept and understand the dynamics between the intellectuals and diplomats who construct the concept of autonomy. For the periodization of this work, we will use three moments in Brazilian history plus the last decade present, with their particular conceptions of autonomy and international insertion, their main intellectuals, and how the idea of autonomy circulated within the field: the period of the Brazilian national developmentalism program, from 1950-1980; the stage of liberal globalization and national-developmentalism (1989-1999) and the phase of the instability of the unipolar global order and the rise of a left-wing party in the government of Brazil (1999-2010).